2022
DOI: 10.5194/wcd-3-1077-2022
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the El Niño teleconnection to the North Atlantic by the tropical North Atlantic during boreal spring and summer

Abstract: Abstract. Equatorial Pacific sea surface temperature anomalies (SSTAs) associated with El Niño–Southern Oscillation (ENSO) can influence the North Atlantic European (NAE) region. ENSO tends to be negatively correlated with the North Atlantic Oscillation in winter, while this connection is less clear in boreal spring and summer when the ENSO teleconnection encounters altered background conditions (i.e., a weaker subtropical jet), which can modulate the signal on the way to the NAE region. One such region that m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Mezzina et al [23] highlighted that the ENSO phenomenon has been shown to contribute to the north Atlantic mid-latitude weather predictability at the surface. Casselman et al [24,25] also confirmed the teleconnection between the ENSO and NAO circulation modes in coupled climatic models. García-Serrano et al [26] revisited the timing of the ENSO-Tropical North Atlantic relationship.…”
Section: Introductionmentioning
confidence: 80%
“…Mezzina et al [23] highlighted that the ENSO phenomenon has been shown to contribute to the north Atlantic mid-latitude weather predictability at the surface. Casselman et al [24,25] also confirmed the teleconnection between the ENSO and NAO circulation modes in coupled climatic models. García-Serrano et al [26] revisited the timing of the ENSO-Tropical North Atlantic relationship.…”
Section: Introductionmentioning
confidence: 80%
“…We use Isca (Vallis et al., 2018), a framework for the idealized modeling of planetary atmospheres, which has previously been used to simulate atmospheric teleconnections (Jiménez‐Esteve & Domeisen, 2019; Thomson & Vallis, 2018a, 2018b), including the ENSO–Europe teleconnection (Casselman et al., 2022; Jiménez‐Esteve & Domeisen, 2020). It uses the Geophysical Fluid Dynamics Laboratory dynamical core along with a number of simplified parameterizations.…”
Section: Methodsmentioning
confidence: 99%
“…There is also some evidence that changing the background climate conditions in the tropical North Atlantic in different seasons might contribute to the modulation of the ENSO signal in the North Atlantic and Europe. For example, the tropical North Atlantic modulates and strengthens the ENSO teleconnection toward the North Atlantic and Europe in boreal spring and summer, respectively (Casselman et al, 2022). López‐Parages and Rodríguez‐Fonseca (2012) pointed out that the AMO modulates the El Niño rainfall teleconnection in the Euro‐Mediterranean region in late winter‐spring, while the PDO modulates it in autumn.…”
Section: Factors Influencing Enso Teleconnectionsmentioning
confidence: 99%